The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1515/cerce-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Using Gelatin to Produce Honey Jelly From Citrus, Clover and Cotton Liquid Honey

Abstract: ABSTRACT. The liquid form of honey is relatively undesirable because honey could be crystallized and then spoilage under certain conditions. In this study, producing honey jelly from liquid citrus, clover and cotton honey using gelatin was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It provides numerous benefits to crop production. It helps to breakup claycompacted soils, improve soil physical properties, assists in transferring micronutrients from the soil to the plant, enhances water retention, increases seed germination rate, improves water, air and root penetration, and stimulates the development of microflora population in soils [20,23]. The application of 1000 mg L −1 of HA reduced the mean germination time of sesame seeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides numerous benefits to crop production. It helps to breakup claycompacted soils, improve soil physical properties, assists in transferring micronutrients from the soil to the plant, enhances water retention, increases seed germination rate, improves water, air and root penetration, and stimulates the development of microflora population in soils [20,23]. The application of 1000 mg L −1 of HA reduced the mean germination time of sesame seeds.…”
Section: Introductionmentioning
confidence: 99%
“…for sesame seeds due to gypsum application, foliar spray of humic acid and/or amino acids [23]. Jahan et al [15] reported the highest and the lowest seed yields of bean (Phaseolus vulgaris L.) were obtained in the application of 80 kg ha −1 SAP + HA and non-application of SAP and HA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of HS on salt and drought tolerances have also been demonstrated in other plant species [11,12]. Foliar spray of HS preparations increased photosynthetic pigment contents in eggplant [13] and the final yield in peanut [14], enhanced tolerance against abiotic stresses [15], improved phytohormone contents in snap bean [16], as well as the fresh and dry weight per plant in common bean [17].…”
Section: Introductionmentioning
confidence: 99%